2016
DOI: 10.1051/epjconf/201610705003
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-induced splitting of the monopole giant resonance in24Mg

Abstract: Abstract. The strong deformation splitting of the isoscalar giant monopole resonance (ISGMR), recently observed in (α, α ) reaction in prolate 24 Mg, is analyzed in the framework of the Skyrme quasiparticle randomphase-approximation (QRPA) approach with the Skyrme forces SkM*, SVbas and SkP δ . The calculations with these forces give close results and confirm that the low-energy E0-peak is caused by the deformation-induced coupling of ISGMR with the K = 0 branch of the isoscalar giant quadrupole resonance.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Results have recently become available for E0 and E2 strengths in 28 Si from calculations in the Skyrme QRPA approach with the SVbas interaction [65]. These results, included in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Results have recently become available for E0 and E2 strengths in 28 Si from calculations in the Skyrme QRPA approach with the SVbas interaction [65]. These results, included in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…[205]. Right panel: The ISGMR strength distributions from RCNP [208] and by Texas A&M [193] data, in comparison with the results from deformed QRPA calculations with Skyrme functionals SkM* and SVbas [208,210]. Figure taken from Ref.…”
Section: Isoscalar Giant Monopole Resonancementioning
confidence: 99%
“…for Sm [6,14], Mo [15] and Cd [16,17] isotopes, and ii) the progress of modern self-consistent mean-field models (relativistic, Skyrme, Gogny) [18,19]. In recent selfconsistent QRPA calculations, the ISGMR in deformed Mg [20][21][22][23], Si [20], Zr [24] and Nd-Sm [25,26] isotopes as well as in 238 U [27] was explored. The results of early studies [8][9][10][11] were generally confirmed.…”
Section: Introductionmentioning
confidence: 99%